2020
DOI: 10.24315/tred.552811
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Yapılandırmacı Öğrenme Ortamı Algıları ve Derse Katılımlarının Demografik Değişkenler Açısından İncelenmesi

Abstract: Bu çalışmanın amacı, ortaokullarda öğrenim gören öğrencilerin yapılandırmacı öğrenme ortamı algısı ve fen bilimleri dersine katımlarının demografik değişkenler açısından değişimini ve bu iki faktör arasındaki ilişkiyi tespit etmektir. Çalışmada nicel araştırma yaklaşımlarından betimsel model kullanılmıştır. Bu doğrultuda çalışmanın örneklemini Erzurum ili Yakutiye ve Aziziye ilçesine bağlı 5 ortaokulda öğrenim gören 206 öğrenci oluşturmaktadır. Çalışmada veri toplama aracı olarak "Yapılandırmacı Öğrenme Ortamı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(13 reference statements)
0
4
0
3
Order By: Relevance
“…Considering the scale sub-dimensions used in the study, secondary school students generally think the science courses offered to them at a certain level of constructivist. In studies conducted with the same scale or with different but similar sub-scales, findings consistent with this result have emerged (Eroğlu, Öner, & Bektaş, 2015;Çavuş, & Yılmaz, 2014;Erdoğan, & Polat, 2017;Mengi, & Schreglman, 2013;Baş, 2012).…”
Section: Extended Abstractmentioning
confidence: 69%
See 4 more Smart Citations
“…Considering the scale sub-dimensions used in the study, secondary school students generally think the science courses offered to them at a certain level of constructivist. In studies conducted with the same scale or with different but similar sub-scales, findings consistent with this result have emerged (Eroğlu, Öner, & Bektaş, 2015;Çavuş, & Yılmaz, 2014;Erdoğan, & Polat, 2017;Mengi, & Schreglman, 2013;Baş, 2012).…”
Section: Extended Abstractmentioning
confidence: 69%
“…On the other hand, the results coincide with the results of Kurt and Bayar's (2020, p.140) study with secondary school students that there is no difference at the grade level. However, some studies have also reported significant differences in this respect (Zorlu, & Zorlu, 2015;Erdoğan, & Polat, 2017;Çavuş, & Yılmaz, 2014). Considering the scale sub-dimensions used in the study, secondary school students generally think the science courses offered to them at a certain level of constructivist.…”
Section: Extended Abstractmentioning
confidence: 99%
See 3 more Smart Citations